A one-year cross sectional study of peritoneal fluid cultures and antibiotic sensitivity patterns in cases of surgical peritonitis - Shah, Nidhi; Malik, Mehnish; Deoleker, S.; Eswar, P. S.; Bhimani, Zulekha (International Surgery Journal, 2025)
Background: Surgical peritonitis is a serious complication with significant morbidity and mortality. Understanding the microbiological profile and antibiotic sensitivity patterns is crucial for optimal management. This study aimed to evaluate the peritoneal fluid cultures and antibiotic sensitivity patterns in cases of surgical peritonitis. Methods: This was a hospital-based prospective study conducted at D. Y. Patil University School of Medicine, Nerul, Navi Mumbai, over a one-year period. Patients presenting with peritonitis were included, and peritoneal fluid samples were collected during surgery for microbiological analysis. Antibiotic treatment was guided by the culture and sensitivity results. Results: A total of 50 patients were enrolled. The most common etiologies were appendicitis (32%), diverticulitis perforation (24%), and perforated duodenal/peptic ulcers (44%). The predominant pathogens isolated from peritoneal fluid cultures were E. coli (16%), Bacteroides fragilis (14%), S. aureus (14%), and Streptococcus anginosus (14%). Antibiotic sensitivity patterns revealed high susceptibility to multiple antibiotics for E. coli, Bacteroides fragilis, and Klebsiella pneumoniae. However, Enterococcus faecalis exhibited concerning resistance to vancomycin and linezolid. Conclusions: This study provides valuable insights into the microbiology and antibiotic susceptibility profiles of pathogens involved in surgical peritonitis cases. The findings can inform empiric antimicrobial treatment strategies and guide antibiotic stewardship efforts in the management of this serious condition.